Intermediate alloy, aluminum alloy, preparation method of intermediate alloy and aluminum alloy and aluminum alloy conductor

By introducing copper-plated carbon components and ceramic particles into the aluminum alloy to form an intermediate alloy, the problems of difficult to take into account the conductivity, strength and heat resistance of existing aluminum alloy materials are solved, and the high conductivity, tensile strength and ultimate heat resistance temperature of aluminum alloy wires are improved.

CN119753458APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410458926.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-15
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing aluminum alloy materials cannot meet the needs of good conductivity, high strength and good heat resistance at the same time, and the interface of the conductive carbon material when combined with Al is unstable, resulting in deterioration of performance.

Method used

An intermediate alloy is used, which contains copper-plated carbon components and aluminum coated with copper-plated carbon components. By forming a copper plating layer on the surface of the conductive carbon material and mixing it with aluminum powder to form a "graphene/copper/aluminum" intermediate alloy, the dispersion uniformity and interface reaction of the conductive carbon material are improved.

Benefits of technology

The aluminum alloy material has excellent electrical conductivity, strength and heat resistance, and the performance degradation caused by interfacial reactions is avoided. This method is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753458A_ABST
    Figure CN119753458A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alloy materials, and discloses an intermediate alloy, an aluminum alloy, a preparation method thereof and an aluminum alloy conductor. The intermediate alloy contains a copper-plated carbon component and aluminum coated outside the copper-plated carbon component, wherein the copper-plated carbon component contains a carbon component and a copper plating layer formed on the surface of the carbon component. The aluminum alloy comprises the following components in percentage by weight: 0.1-2.5% of a copper-plated carbon component, 0.1-2% of a ceramic component, less than or equal to 0.1% of Si, less than or equal to 0.25% of Fe, 0.01-0.1% of B, 0.005-0.05% of rare earth elements, less than or equal to 0.1% of inevitable impurities and the balance of Al. The intermediate alloy provided by the invention can effectively improve the function of a conductive carbon material as a conductive reinforcement, the fine ceramic particles improve the thermal stability of the material, and finally the aluminum alloy has excellent heat resistance, relatively high strength and excellent conductivity at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, and in particular to a master alloy and an aluminum alloy and a preparation method thereof, and an aluminum alloy wire. Background Art

[0002] Aluminum conductors require materials to have both good strength and conductivity to meet the requirements of long-span and large-capacity power transmission, as well as heat resistance that does not soften during long-term operation. However, the strength and heat resistance of the material are contradictory to the conductivity in the composition design. The existing technology hopes that the alloy has higher heat resistance and conductivity. Although pure aluminum has good conductivity, it has low strength and poor heat resistance. In order to meet the requirements of heat resistance, strength, and conductivity, there are currently two ideas for high-strength, heat-resistant, and conductive aluminum alloys: one is to add Zr elements to 1 series or 6 series alloys to precipitate ZrAl3 to improve strength and heat resistance, and to cooperate with the purification effect of rare earth elements to reduce melt impurities or reduce the solid solubility of impurities in aluminum to ensure conductivity. By adding precipitation-strengthened limited Zr elements, ZrAl3 is precipitated in situ in the aluminum melt. The ability of Zr to dissolve and then precipitate ZrAl3 is limited, so the heat resistance is limited. The second is to introduce particle reinforcement into the alloy to overcome the contradiction that ZrAl3 is limited in strengthening and is not conducive to conductivity. There are many aluminum composite materials, especially graphene aluminum composite materials, which have excellent conductivity. However, when graphene is directly added to aluminum melt, it is easy to agglomerate and disperse unevenly, and it is easy to produce easily hydrolyzed Al3C4 at the interface with the aluminum melt, which ultimately deteriorates the material performance and does not play a positive role.

[0003] Existing aluminum alloys cannot simultaneously meet the requirements of good conductivity, high strength and good heat resistance. Therefore, there is an urgent need to develop an aluminum alloy material with excellent heat resistance, high strength and excellent conductivity. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the improvement of heat resistance and strength of existing aluminum alloy materials depends on the addition of elements such as Zr, Mg, Cu, etc. that can cause precipitation strengthening, and the existing aluminum alloys cannot simultaneously meet the performance of heat resistance, strength and conductivity, and provide a master alloy and aluminum alloy and a preparation method thereof and an aluminum alloy wire. The master alloy provided by the present invention can effectively improve the function of the conductive carbon material as a conductive reinforcement, and the aluminum alloy has excellent heat resistance, high strength and excellent conductivity.

[0005] In order to achieve the above objectives, the present invention provides an intermediate alloy on one hand, which contains a copper-plated carbon component and aluminum coated outside the copper-plated carbon component, wherein the copper-plated carbon component contains a carbon component and a copper plating layer formed on the surface of the carbon component.

[0006] Preferably, in the master alloy, the content of the copper-plated carbon component is ≤40% by volume, with aluminum being the balance.

[0007] Preferably, in the copper-plated carbon component, the mass fraction of Cu element on the surface of the carbon component is 35-60%.

[0008] Preferably, the carbon component is graphene and / or carbon nanotubes.

[0009] A second aspect of the present invention provides a method for preparing a master alloy, the method comprising:

[0010] (1) forming a copper plating layer on the surface of the conductive carbon material to obtain a modified conductive carbon material;

[0011] (2) Mixing the modified conductive carbon material with aluminum powder, making embryos, and sintering.

[0012] Preferably, in step (1), the conductive carbon material is graphene and / or carbon nanotubes.

[0013] Preferably, the graphene sheet has a diameter of 10-25 μm and a thickness of ≤50 nm.

[0014] Preferably, the carbon nanotubes have a diameter of 2-10 nm and a length of 1-20 μm.

[0015] In step (1), the process of forming a copper plating layer on the surface of the conductive carbon material comprises: purifying and dispersing, roughening, sensitizing, activating and chemically copper plating the conductive carbon material in sequence.

[0016] Preferably, the operating conditions of the chemical copper plating include: the pH value of the chemical plating solution is 11.5-12, the temperature of the chemical plating is 45-100° C., and the time is 30-70 min.

[0017] Preferably, in step (2), based on the total amount of the modified conductive carbon material and the aluminum powder, the amount of the modified conductive carbon material is 20-40% by volume.

[0018] Preferably, in step (2), the particle size of the aluminum powder is ≤100 um.

[0019] Preferably, in step (2), the sintering conditions include: temperature of 400-600° C. and time of 0.5-1.5 h.

[0020] The third aspect of the present invention provides an aluminum alloy raw material composition, which contains aluminum blocks, aluminum alloy blocks, ceramic particles and intermediate alloys; the intermediate alloy is the intermediate alloy described above or the intermediate alloy prepared by the method described above.

[0021] Preferably, the ceramic particles are selected from one or more of AlN, B4C and TiC.

[0022] Preferably, the particle size of the ceramic particles is 10-50 nm.

[0023] The fourth aspect of the present invention provides an aluminum alloy, which is prepared from the composition described above, and contains 0.1-2.5 weight % of copper-plated carbon components, 0.1-2 weight % of ceramic components, ≤0.1 weight % of Si, ≤0.25 weight % of Fe, 0.01-0.1 weight % of B, 0.005-0.05 weight % of rare earth elements, ≤0.1 weight % of unavoidable impurities and the balance weight % of Al.

[0024] Preferably, the carbon component in the copper-plated carbon component is graphene and / or carbon nanotubes.

[0025] Preferably, the ceramic component is selected from one or more of AlN, B4C and TiC.

[0026] Preferably, the rare earth element is selected from one or more of Er, La, Ce and Y.

[0027] A fifth aspect of the present invention provides a method for preparing the aluminum alloy mentioned above, the method comprising: melting an aluminum block, an aluminum alloy block, ceramic particles and an intermediate alloy.

[0028] Preferably, the smelting process comprises: melting the aluminum block, the aluminum alloy block, the ceramic particles and the master alloy at 680-730°C, and then refining at 650-750°C.

[0029] A sixth aspect of the present invention provides an aluminum alloy wire, which is made of the aluminum alloy described above or an aluminum alloy prepared by the method described above.

[0030] Preferably, the aluminum alloy wire has a conductivity of ≥60% IACS, a tensile strength of ≥270 MPa, a maximum heat-resistant temperature of ≥310° C., and an elongation of ≥1%.

[0031] Compared with the prior art, the present invention has at least the following beneficial effects:

[0032] (1) The intermediate alloy provided by the present invention contains a carbon component, a copper coating on the carbon component, and an aluminum component coated outside the carbon component and the copper coating. The conductive carbon material is smelted in the form of the intermediate alloy to prepare an aluminum alloy, which can protect the conductive carbon material and solve the problem of interface instability when the conductive carbon material and Al are composited, thereby effectively improving the function of the conductive carbon material as a conductive enhancer.

[0033] (2) The present invention optimizes the formula of aluminum alloy and specifically combines specific carbon components and ceramic components with other components, so that the aluminum alloy of the present invention has excellent heat resistance, high strength, and excellent electrical conductivity. Among them, the carbon component has good electrical conductivity and can alleviate the contradiction between strength and conductivity as a conductive reinforcement; the ceramic component as a single reinforcement can greatly improve the heat resistance and strength of the aluminum alloy without relying on elements such as Zr, Mg, and Cu with limited strengthening effects.

[0034] (3) The method described in the present invention introduces conductive carbon materials through an intermediate alloy and adopts a casting method to prepare aluminum alloys. On the one hand, it can avoid the interface reaction to form Al3C4 resulting in high interface resistance, and can also protect the conductive carbon materials, thereby maximizing the function of the conductive carbon materials as conductive enhancers; on the other hand, it can prevent the conductive carbon materials from agglomerating and improve the uniformity of the conductive carbon materials in the aluminum liquid; on the third hand, it can solve the problem of interface instability when the conductive carbon materials and Al are compounded, thereby making the industrial production of conductive carbon material modified aluminum alloy materials possible. The method described in the present invention can significantly improve the heat resistance and strength of the prepared aluminum alloy by introducing ceramic particles.

[0035] (4) The method provided by the present invention can prepare aluminum alloy materials with excellent heat resistance, high strength and excellent electrical conductivity, without the need to add elements such as Zr, Mg, Cu, etc. that can cause precipitation strengthening but have limited strengthening effects, and the method can be realized on a large scale industrially.

[0036] (5) The aluminum alloy wire of the present invention has excellent heat resistance, high strength, excellent electrical conductivity, and good elongation. Specifically, the aluminum alloy wire has an electrical conductivity of ≥60% IACS, a tensile strength of ≥270 MPa, an ultimate heat-resistant temperature of ≥310°C, and an elongation of ≥1%. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a flowchart of a method for preparing an aluminum alloy wire according to one embodiment of the present invention. DETAILED DESCRIPTION

[0038] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0039] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0040] The first aspect of the present invention provides a master alloy, which contains a copper-plated carbon component and aluminum coated on the outside of the copper-plated carbon component, wherein the copper-plated carbon component contains a carbon component and a copper coating formed on the surface of the carbon component, wherein the aluminum exists in a single substance.

[0041] The intermediate alloy described in the present invention is a coating structure material. When the intermediate alloy is used to prepare aluminum alloy, a Cu film is formed at the interface between the conductive carbon material (carbon component) and Al under this structure, which avoids the high interface resistance caused by the formation of Al3C4 due to interface reaction, protects the conductive carbon material, and solves the problem of interface instability when the conductive carbon material and Al are composited, thereby effectively improving the function of the conductive carbon material as a conductive enhancer.

[0042] In a specific embodiment, in the master alloy, the content of the copper-plated carbon component is ≤40% by volume, with aluminum being the balance. In a preferred embodiment, in order to improve the electrical conductivity of the aluminum alloy and to minimize the agglomeration of carbon particles, the content of the copper-plated carbon component in the master alloy is 5 to 25% by volume.

[0043] In the master alloy of the present invention, the content of Cu is relatively small and distributed on the surface of the copper-plated carbon component. In a specific embodiment, micro-area element analysis using EDS energy spectrum analysis shows that in the copper-plated carbon component, the mass fraction of Cu element on the surface of the carbon component is 35-60%.

[0044] In the present invention, the carbon component can be a material with a conductive function commonly used in the art. In a specific embodiment, the carbon component can be graphene and / or carbon nanotubes. In a preferred embodiment, the carbon component is graphene.

[0045] A second aspect of the present invention provides a method for preparing a master alloy, the method comprising:

[0046] (1) forming a copper plating layer on the surface of the conductive carbon material to obtain a modified conductive carbon material;

[0047] (2) Mixing the modified conductive carbon material with aluminum powder, making embryos, and sintering.

[0048] The present invention creatively plates copper on the conductive carbon material and then coats it with aluminum powder to obtain a "graphene / copper / aluminum" intermediate alloy that is uniformly distributed in the aluminum matrix and has good interface bonding. The use of the intermediate alloy to prepare aluminum alloy can improve the dispersion uniformity of the conductive carbon material in the aluminum liquid and the problem of interface reaction Al3C4 to the greatest extent, thereby making the industrial production of conductive carbon material modified aluminum wire cables possible.

[0049] In the present invention, the copper-coated conductive carbon material obtained by chemical copper plating cannot be directly used to prepare aluminum alloys, and it is necessary to further use aluminum powder for coating. The main reason is: if aluminum powder is not used for further coating, the copper-coated carbon powder is difficult to disperse in the aluminum liquid due to the density difference, and the Cu film is directly in contact with the aluminum solution, resulting in poor wetting of the particle surface and the aluminum melt. By mixing, embryo making, and sintering the copper-plated conductive carbon material and aluminum powder, chemical diffusion can be generated at the Cu-Al interface to achieve the metallurgical bonding of Cu-Al, that is, a layer of aluminum is coated on the surface of the copper-coated conductive carbon material, and the material finally obtained can be added to the Al melt in a manner similar to conventional master alloys, and the traditional powder metallurgy method for preparing composite materials is optimized into a melting and casting method suitable for industrial scale. At the same time, in the present invention, if aluminum-coated conductive carbon material is directly used, Al is in direct contact with graphene, which will destroy the interface and introduce resistance, resulting in poor conductivity of the aluminum alloy. Therefore, in the present invention, the conductive carbon material needs to be coated in a specific order.

[0050] In a specific embodiment, the process of forming a copper plating layer on the surface of the conductive carbon material in step (1) comprises: purifying and dispersing, roughening, sensitizing, activating and chemically copper plating the conductive carbon material in sequence.

[0051] The purpose of purification and dispersion is to remove organic impurities on the surface of the conductive carbon material due to the surface molecular adsorption force; dispersion is due to the fact that the conductive carbon material, especially the graphene, has a large intermolecular force and is easy to aggregate, so it is necessary to disperse. In the present invention, the purification and dispersion can be carried out according to conventional operations in the field. In a specific embodiment, the purification and dispersion process of the conductive carbon material includes: the conductive carbon material is ultrasonically cleaned and stirred in acetone and / or anhydrous ethanol for 0.5-2h to clean and disperse the organic matter remaining on its surface, and the purified and dispersed graphene is fully filtered and washed in distilled water under centrifugal force to ensure that the pH value is neutral.

[0052] The purpose of roughening is to chemically roughen the surface of the conductive carbon material, form hydrophilic functional groups on the surface of the conductive carbon material so that it has a certain hydrophilicity and roughness, and ensure the adhesion and uniformity of the copper plating. In the present invention, the conductive carbon material can be roughened by acid washing and oxidation. In a specific embodiment, the roughening process includes: mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 to prepare a roughening solution, cooling the roughening solution to room temperature and then immersing the purified and dispersed conductive carbon material, using ultrasonic dispersion treatment for 10-20 minutes before and after the heating reaction, the heating temperature is 130-180°C, and the heating time is 1-4h. After the roughening is completed, distilled water is used for filtration and washing to ensure a neutral pH value.

[0053] The role of sensitization is to adsorb a layer of reducing divalent Sn on the surface of the roughened conductive carbon material. 2+ In a specific embodiment, the sensitization process includes: preparing a sensitizing solution by mixing 3-6 mL of 90-96 mass % hydrochloric acid, 2-4 g of SnCl2, and 90-120 mL of distilled water, soaking the roughened conductive carbon material in the sensitizing solution for 40-60 minutes, and then filtering and washing with distilled water.

[0054] The activation process is to form a layer of single substance Ag on the surface of the conductive carbon material, forming a uniform catalytic activation point, which is convenient for the subsequent chemical copper plating to proceed spontaneously. In a specific embodiment, the activation process includes: preparing an activation solution with 0.3-0.8g of AgNO3, 1-2mL of NH3.H2O, and 40-60mL of distilled water, immersing the sensitized conductive carbon material in the activation solution to make the surface of the conductive carbon material Sn 2+ and Ag + Oxidation-reduction reaction occurs to generate single substance Ag, forming activation points of the coating. The reaction formula is Sn 2+ +2Ag + =2Ag+Sn 4+ .

[0055] In a specific embodiment, the operating conditions of the chemical copper plating include: the pH value of the chemical plating solution is 11.5-12, the temperature of the chemical plating is 45-100°C, and the time is 30-70min. In the present invention, there is no special restriction on the composition of the chemical plating solution, and it can be selected according to conventional operations. In a more specific embodiment, the process of chemical copper plating includes: preparing a chemical plating solution with a pH value of 11.5-12 with formaldehyde, C4H4Na2O6, CuSO4.5H2O, NaCO3, NaOH and distilled water, and then placing the activated conductive carbon material in the chemical plating solution at 45-100°C and stirring for 30-70min, cooling to room temperature, and filtering and vacuum drying to obtain a conductive carbon material with copper plated on the surface.

[0056] In the method of the present invention, the amount of Sn and Ag introduced during the sensitization and activation process is small, cannot be detected, and can be ignored. The amount of Cu introduced during chemical copper plating is also small.

[0057] In the method of the present invention, the conductive carbon material can be a material with good conductivity known in the art. In a specific embodiment, the conductive carbon material can be graphene and / or carbon nanotubes. In a preferred embodiment, in order to further improve the conductivity of the prepared aluminum alloy, the conductive carbon material is graphene.

[0058] In a preferred embodiment, the diameter of the graphene sheet is 10-25 μm. When the diameter of the graphene sheet exceeds 25 μm, the dispersion step before chemical copper plating is difficult to complete. When the diameter of the graphene sheet is greater than 10 μm, the conductivity of the aluminum alloy is greatly improved. In the present invention, the thickness of the graphene is as small as possible. In a preferred embodiment, the thickness of the graphene is ≤50 nm.

[0059] In a preferred embodiment, the carbon nanotubes have a diameter of 2-10 nm and a length of 1-20 μm.

[0060] In step (2) of the present invention, the specific process of coating the modified conductive carbon material obtained after surface copper plating with aluminum powder includes: ultrasonically dispersing the modified conductive carbon material, and then mixing it with aluminum powder under a protective atmosphere to obtain a slurry, the slurry is filtered, vacuum dried and cold pressed to obtain a block powder embryo, and the block powder embryo is sintered in a sintering furnace to obtain an intermediate alloy.

[0061] In a specific embodiment, based on the total amount of the modified conductive carbon material and the aluminum powder, the amount of the modified conductive carbon material can be 20-40 volume %.

[0062] In the present invention, the amount of the aluminum powder is not particularly limited, as long as it can form an aluminum film on the surface of the modified conductive carbon material. In order to avoid the modified conductive carbon material and the aluminum powder from agglomerating due to the large difference in particle size between the modified conductive carbon material and the aluminum powder, which leads to the conductive carbon material having a larger specific surface area than the aluminum powder, thus causing uneven mixing, the particle size of the aluminum powder should not be too large. In a preferred embodiment, the particle size of the aluminum powder in step (2) is ≤100um.

[0063] In a specific embodiment, the protective atmosphere can be an inert atmosphere such as argon, nitrogen, etc., or can be a vacuum or low-oxygen environment.

[0064] In the method of the present invention, the mixing method in step (2) can be ball milling. In a specific embodiment, the operating conditions of the ball milling include: a ball-to-material ratio of 3-8:1, paraffin as a binder, anhydrous ethanol and / or acetone as a medium, a rotation speed of 120-160 r / min, and a ball milling time of 30-60 h.

[0065] In step (2), the sintering is performed under low temperature and pressure conditions. In a specific embodiment, the sintering temperature can be 400-600° C., and the sintering time can be 0.5-1.5 hours.

[0066] The third aspect of the present invention provides an aluminum alloy raw material composition, which contains aluminum blocks, aluminum alloy blocks, ceramic particles and intermediate alloys; the intermediate alloy is the intermediate alloy described above or the intermediate alloy prepared by the method described above.

[0067] In the present invention, the intermediate alloy is combined with an aluminum block, an aluminum alloy block and ceramic particles for smelting to prepare an aluminum alloy, which can protect the conductive carbon material and solve the problem of interface instability when the conductive carbon material and Al are composited, thereby effectively improving the function of the conductive carbon material as a conductive enhancer.

[0068] In a specific embodiment, the ceramic particles may be selected from one or more of AlN, B4C and TiC. In a preferred embodiment, the particle size of the ceramic particles may be 10-50 nm.

[0069] In the present invention, the amounts of the aluminum block, the aluminum alloy block, the ceramic particles and the master alloy are proportioned and adjusted according to the weight percentage of each component in the target product aluminum alloy.

[0070] The fourth aspect of the present invention provides an aluminum alloy, which is prepared from the composition described above, and contains 0.1-2.5% by weight of a copper-plated carbon component, 0.1-2% by weight of a ceramic component, ≤0.1% by weight of Si, ≤0.25% by weight of Fe, 0.01-0.1% by weight of B, 0.005-0.05% by weight of rare earth elements, ≤0.1% by weight of unavoidable impurities and the remainder of Al. The inventors of the present invention have found through research that by introducing a specific content of a copper-plated carbon component (a carbon component with copper plated on the surface) and a ceramic component into the aluminum alloy, and limiting the content of other components within a specific range, the aluminum alloy can have excellent heat resistance, high strength and excellent electrical conductivity at the same time.

[0071] In the aluminum alloy of the present invention, the content of Cu is relatively small and distributed on the surface of the copper-plated carbon component. In a specific embodiment, micro-area element analysis using EDS energy spectrum analysis shows that in the copper-plated carbon component, the mass fraction of Cu element on the surface of the carbon component is 35-60%.

[0072] In a specific embodiment, the carbon component in the copper-plated carbon component can be a component with good conductivity well known in the art, for example, the carbon component can be graphene and / or carbon nanotubes. In a preferred embodiment, in order to further improve the electrical conductivity of the aluminum alloy, the carbon component is graphene. In the present invention, the carbon component mainly plays a conductive enhancement role, improving the electrical conductivity of the aluminum alloy. If the content of the carbon component is too low, the electrical conductivity of the aluminum alloy is poor; if the content of the carbon component is too high, the elongation of the aluminum alloy is low, so the content of the copper-plated carbon component is limited to 0.1-2.5 weight%.

[0073] In a specific embodiment, the ceramic component can be selected from one or more of AlN, B4C and TiC. In the present invention, the ceramic component, as a separate reinforcement, mainly plays a second phase strengthening function, which can greatly improve the heat resistance and strength of the aluminum alloy. If the content of the ceramic component is too low, the heat resistance and strength of the aluminum alloy are low; if the content of the ceramic component is too high, additional resistance will be increased, and the elongation and toughness of the aluminum alloy will be low, which is not conducive to subsequent drawing. When the ceramic component is AlN, the content of the ceramic component is 0.2-1% by weight. When the ceramic component is B4C, the content of the ceramic component is 0.28-1.41% by weight. When the ceramic component is TiC, the content of the ceramic component is 0.16-0.78% by weight.

[0074] Si is a basic impurity element in aluminum alloys and the most important impurity element affecting the electrical conductivity of aluminum alloys. In the present invention, the content of Si in the aluminum alloy can be controlled to be ≤0.1 wt%.

[0075] Fe is also a basic impurity element in aluminum alloys, and is an inevitable impurity in the actual production of aluminum alloys. In actual production, the Fe content is controlled so that it reacts with the impurity Si to form α-Al8Fe2Si, while preventing Fe from generating additional resistance β-Al3Fe. Therefore, the Fe / Si weight ratio of 2-3 has little effect on the conductive properties of the aluminum alloy. Therefore, in the present invention, the Fe content in the aluminum alloy is controlled to be ≤0.25% by weight.

[0076] Ti, V, Mn and Cr are transition trace impurity elements in aluminum alloys, which have a great influence on the electrical conductivity of aluminum alloys. Trace amounts of B can react with trace amounts of transition elements to form insoluble high-temperature resistant borides and settle at the bottom of the furnace, so that they precipitate from the solid solution state, thereby improving the electrical conductivity of the aluminum alloy. Therefore, in order to make the electrical conductivity of the aluminum alloy higher, the present invention controls the content of B to 0.01-0.1 weight %.

[0077] In a specific embodiment, the rare earth element can be a conventional choice in the art, for example, the rare earth element can be selected from one or more of Er, La, Ce and Y. The main function of the rare earth element is to react with Fe and Si to precipitate, improve the precipitation distribution of Fe and Si, and reduce the adverse effects of Fe and Si on the electrical conductivity of the aluminum alloy. The rare earth element also has conventional functions such as grain refinement. Compared with not adding rare earth, it can improve the electrical conductivity and strength of the aluminum alloy, but the negative effect of reducing the electrical conductivity of Fe and Si is limited, and adding too much is prone to pores after the aluminum alloy solidifies, so the content of the rare earth element should not be too high. Therefore, in the present invention, the content of the rare earth element can be controlled to be 0.005-0.05% by weight.

[0078] A fifth aspect of the present invention provides a method for preparing the aluminum alloy as described above, the method comprising:

[0079] Aluminum blocks, aluminum alloy blocks, ceramic particles and master alloys are melted.

[0080] In the present invention, the components added in the smelting process are proportioned according to the weight percentage of the components in the aforementioned aluminum alloy.

[0081] In a specific embodiment, the ceramic particles may be selected from one or more of AlN, B4C and TiC. In a preferred embodiment, the particle size of the ceramic particles may be 10-50 nm.

[0082] In the method of the present invention, the smelting process in step (3) comprises: melting the aluminum block, the aluminum alloy block, the ceramic particles and the intermediate alloy at 680-730°C, and then refining at 650-750°C.

[0083] In the present invention, the aluminum alloy block is added in the form of Al-X master alloy, wherein X is each alloy element, for example, when X is Si, the aluminum alloy block is an Al-Si alloy block, and when X is B, the aluminum alloy block is an Al-B alloy block.

[0084] In the present invention, after obtaining the aluminum alloy liquid, the aluminum alloy liquid can be prepared into other aluminum alloy products through other processes according to actual needs. In a specific embodiment, the aluminum alloy liquid can be sequentially obtained into aluminum ingots, aluminum rods and aluminum wires through continuous casting, continuous rolling and drawing.

[0085] The method of the present invention alleviates the existing design contradiction between electrical conductivity and heat resistance and strength. The heat resistance does not rely on elements such as Zr with limited strengthening effect. The conductive reinforcement adopts the method of intermediate alloy to realize the scalable preparation of conductive materials by casting method. The aluminum alloy does not need aging treatment after wire drawing. The product prepared by the present invention has better heat resistance and electrical conductivity, low manufacturing cost, simple and safe process.

[0086] A sixth aspect of the present invention provides an aluminum alloy wire, which is made of the aluminum alloy described above.

[0087] In a specific implementation, the aluminum alloy wire has a conductivity of ≥60% IACS, a tensile strength of ≥270 MPa, an ultimate heat-resistant temperature of ≥310° C., and an elongation of ≥1%.

[0088] In the present invention, the conductivity is tested with reference to the "Conductivity Test Standard GB / T 3955-2009 Electrical Round Aluminum Wire". The elongation is tested according to the "Mechanical Test Standard GB / T 228.1-2010 Metal Material Tensile Test". The tensile strength is tested with reference to the "Mechanical Test Standard GB / T 228.1-2010 Metal Material Tensile Test".

[0089] In the present invention, the test method of the ultimate heat-resistant temperature is: the aluminum alloy wire is kept at different temperatures for 1 hour, then cooled to room temperature, and its tensile strength is tested as T1, and its tensile strength before heating and heat preservation is T0, and the high-temperature retention rate of strength is calculated, wherein the calculation method of the high-temperature retention rate of strength is T1÷T0×100%, and when the high-temperature retention rate of strength is greater than 90%, the corresponding highest temperature is taken as its ultimate heat-resistant temperature. For example, the aluminum alloy wire is kept at 180-350℃ for 1 hour, cooled to room temperature, and the tensile strength obtained is compared with the tensile strength under the condition of no heating and heat preservation. It is found that when the heating and heat preservation temperature is 310℃, the strength retention rate is 90.70%, which is greater than 90%, that is, the heat-resistant temperature of the aluminum alloy wire is 310℃.

[0090] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0091] In the following examples, unless otherwise specified, the methods and processes involved are all routine operations in the art; unless otherwise specified, the raw materials used are all commonly available commercial products in the art.

[0092] Examples A1-A3 are used to illustrate the preparation process of the master alloy.

[0093] Example A1

[0094] S1. Purification and dispersion: Graphene powder with a flake diameter of 18 μm and a thickness of 30 nm is cleaned and stirred in acetone by ultrasonic cleaning for 1 h to clean the organic matter remaining on the surface and disperse it. The purified and dispersed graphene is fully filtered and washed in distilled water under centrifugal force until the pH value is neutral;

[0095] S2, roughening: concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 1:1 to prepare a roughening solution, the roughening solution is cooled to room temperature, and the purified and dispersed graphene is immersed in it, and ultrasonic dispersion treatment is performed for 15 minutes before and after the heating reaction, wherein the conditions of the heating reaction include: heating temperature 150°C, heating time 2h, and after the roughening is completed, distilled water is used for filtration and washing until the pH value is neutral;

[0096] S3, sensitization: 5mL, 96 mass% hydrochloric acid, 3g SnCl2, 100mL distilled water are prepared as a sensitizing solution, the roughened graphene is soaked in the sensitizing solution for 50min, and after soaking, it is filtered and washed with distilled water;

[0097] S4, activation: 0.5g AgNO3, 1.5mL NH 3· H2O and 50mL of distilled water were prepared as an activation solution, and the sensitized graphene was immersed in the activation solution for 40 minutes to form activation points of the coating;

[0098] S5, chemical copper plating: formaldehyde, C4H4Na2O6, CuSO4.5H2O, NaCO3, NaOH and distilled water are prepared into a chemical plating solution with a pH value of 11.8, and then the activated graphene is placed in the chemical plating solution and stirred continuously at 80°C for 1 hour, cooled to room temperature, and filtered and vacuum dried to obtain copper-plated graphene;

[0099] S6. Mixing, embryo making and sintering of copper-plated graphene and aluminum powder (particle size ≤ 100um): The copper-plated graphene is ultrasonically dispersed and then mixed with aluminum powder by ball milling under argon. The ball milling conditions include: ball-to-material ratio of 5:1, the volume fraction of copper-plated graphene is 30%, paraffin is used as a binder, anhydrous ethanol is used as a medium, the rotation speed is 150r / min, and the ball milling time is 48h to obtain a slurry. The slurry is filtered, vacuum dried and cold pressed to obtain a block powder embryo. The block powder embryo is sintered in a sintering furnace at a temperature of 520°C for 1h to obtain an intermediate alloy A1, in which the volume fraction of the copper-plated graphene is 25% and the balance is aluminum.

[0100] In step S5, EDS energy spectrum analysis is used to perform micro-area element analysis on the copper-plated graphene, and the Cu mass fraction on the graphene surface is 70% to 75%; EDS energy spectrum analysis is used to perform micro-area element analysis on the graphene surface in the intermediate alloy A1, and the Cu mass fraction on the graphene surface is 45% to 50%.

[0101] Example A2

[0102] S1. Purification and dispersion: Graphene powder with a diameter of 25 μm and a thickness of 50 nm was ultrasonically cleaned and stirred in acetone for 2 h to clean and disperse the organic matter remaining on its surface. The purified and dispersed graphene was fully filtered and washed in distilled water under centrifugal force until the pH value was neutral;

[0103] S2, roughening: Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 1:1 to prepare a roughening solution, the roughening solution is cooled to room temperature, and the purified and dispersed graphene is immersed in it, and ultrasonic dispersion treatment is performed for 20 minutes before and after the heating reaction, wherein the conditions of the heating reaction include: heating temperature 180°C, heating time 1h, and after the roughening is completed, distilled water is used for filtration and washing until the pH value is neutral;

[0104] S3, sensitization: 6 mL, 96 mass% hydrochloric acid, 4 g SnCl2, 100 mL distilled water are prepared as a sensitizing solution, the roughened graphene is soaked in the sensitizing solution for 30 min, and after soaking, it is filtered and washed with distilled water;

[0105] S4, activation: 0.8g of AgNO3, 2mL of NH 3· H2O and 60 mL of distilled water were prepared as an activation solution, and the sensitized graphene was immersed in the activation solution for 1 hour to form activation points of the coating;

[0106] S5, chemical copper plating: formaldehyde, C4H4Na2O6, CuSO4.5H2O, NaCO3, NaOH and distilled water are prepared into a chemical plating solution with a pH value of 11.8, and then the activated graphene is placed in the chemical plating solution and stirred continuously at 60°C for 0.5 hours, cooled to room temperature, and filtered and vacuum dried to obtain copper-plated graphene;

[0107] S6. Mixing, embryo making and sintering of copper-plated graphene and aluminum powder (particle size ≤ 100um): The copper-plated graphene is ultrasonically dispersed and then mixed with aluminum powder by ball milling under argon. The ball milling conditions include: ball-to-material ratio of 5:1, the volume fraction of copper-plated graphene is 40%, paraffin is used as a binder, anhydrous ethanol is used as a medium, the rotation speed is 150r / min, and the ball milling time is 48h to obtain a slurry. The slurry is filtered, vacuum dried and cold pressed to obtain a block powder embryo. The block powder embryo is sintered in a sintering furnace at a temperature of 550°C for 1.5h to obtain an intermediate alloy A2, in which the volume fraction of the copper-plated graphene is 35% and the balance is aluminum.

[0108] In step S5, EDS energy spectrum analysis is used to perform micro-area element analysis on the copper-plated graphene, and the Cu mass fraction on the graphene surface is 65% to 70%; EDS energy spectrum analysis is used to perform micro-area element analysis on the graphene surface in the intermediate alloy A2, and the Cu mass fraction on the graphene surface is 40% to 45%.

[0109] Example A3

[0110] S1. Purification and dispersion: Graphene with a sheet diameter of 10 μm and a thickness of 50 nm is ultrasonically cleaned and stirred in acetone for 1.5 h to clean and disperse the organic matter remaining on the surface. The purified and dispersed graphene is fully filtered and washed in distilled water under centrifugal force until the pH value is neutral;

[0111] S2, roughening: Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 1:1 to prepare a roughening solution, the roughening solution is cooled to room temperature, and the purified and dispersed graphene is immersed in it. Ultrasonic dispersion treatment is performed for 10 minutes before and after the heating reaction, wherein the conditions of the heating reaction include: heating temperature 160°C, heating time 1.5h, and after the roughening is completed, distilled water is used for filtration and washing until the pH value is neutral;

[0112] S3, sensitization: 5mL, 96 mass% hydrochloric acid, 3g SnCl2, 100mL distilled water are prepared as a sensitizing solution, the roughened graphene is soaked in the sensitizing solution for 40min, and after soaking, it is filtered and washed with distilled water;

[0113] S4, activation: 0.5g AgNO3, 1.5mL NH 3· 50 mL of H2O and distilled water were used as an activation solution, and the sensitized graphene was immersed in the activation solution for 1.5 hours to form activation points for the coating;

[0114] S5, chemical copper plating: formaldehyde, C4H4Na2O6, CuSO4.5H2O, NaCO3, NaOH and distilled water are prepared into a chemical plating solution with a pH value of 11.8, and then the activated graphene is placed in the chemical plating solution and stirred continuously at 80°C for 1 hour, cooled to room temperature, and filtered and vacuum dried to obtain copper-plated graphene;

[0115] S6. Mixing, embryo making and sintering of copper-plated graphene and aluminum powder (particle size ≤ 100um): The copper-plated graphene is ultrasonically dispersed and then mixed with aluminum powder by ball milling under argon. The ball milling conditions include: ball-to-material ratio of 5:1, the volume fraction of copper-plated graphene is 10%, paraffin is used as a binder, anhydrous ethanol is used as a medium, the rotation speed is 150r / min, and the ball milling time is 48h to obtain a slurry. The slurry is filtered, vacuum dried and cold pressed to obtain a block powder embryo. The block powder embryo is sintered in a sintering furnace at a temperature of 500°C for 1h to obtain an intermediate alloy A3, in which the volume fraction of copper-plated graphene is 10% and the balance is aluminum.

[0116] In step S5, EDS energy spectrum analysis is used to perform micro-area element analysis on the copper-plated graphene, and the Cu mass fraction on the graphene surface is 75% to 80%; EDS energy spectrum analysis is used to perform micro-area element analysis on the graphene surface in the intermediate alloy A3, and the Cu mass fraction on the graphene surface is 50%-55%.

[0117] Examples B1-B20 are used to illustrate the preparation process of aluminum alloy wires.

[0118] Example B1

[0119] The aluminum alloy wire of this embodiment contains the following components: 0.9 wt% copper-plated graphene, 0.6 wt% aluminum nitride, 0.07 wt% Si, 0.08 wt% Fe, 0.05 wt% B, 0.01 wt% rare earth element (Ce), ≤0.1 wt% unavoidable impurities, and aluminum as the balance.

[0120] The preparation method of aluminum alloy wire includes smelting, continuous casting, continuous rolling, and cold drawing. The specific process includes:

[0121] According to the composition and content of the aluminum alloy wire, the aluminum block is melted at 700°C, and then aluminum nitride particles (AlN with a particle size of 40nm) and intermediate alloy A1 are added and stirred; then the aluminum alloy liquid is refined and deslagging is obtained at 720°C; the aluminum alloy liquid is introduced into a continuous casting machine to be cast into an aluminum alloy continuous casting billet; the aluminum alloy continuous casting billet is heated to 465°C by a medium frequency induction heater to soften the aluminum ingot; the continuous casting billet is sent to a continuous rolling mill for continuous rolling into an aluminum alloy round rod with a diameter of 9 mm, and the aluminum alloy round rod is cooled to room temperature through water; the aluminum alloy round rod is drawn into an aluminum alloy wire with a diameter of 1-3 mm.

[0122] Example B2-Example B16

[0123] An aluminum alloy wire was prepared according to the method of Example 1, except for the content of each component in the aluminum alloy wire. The formulas of Example B2 to Example B16 are shown in Table 1.

[0124] Table 1

[0125]

[0126] Example B17

[0127] The method of Example B1 was followed, except that the ceramic particles were replaced with TiC instead of AlN.

[0128] Example B18

[0129] The method of Example B1 was followed, except that the ceramic particles were replaced with B4C instead of AlN.

[0130] Example B19

[0131] The method of Example B1 is followed, except that the component composition and content ratio of the aluminum alloy wire are changed. Specifically, the aluminum alloy wire of this example contains the following components: 0.1 wt% copper-plated graphene, 2 wt% aluminum nitride, 0.1 wt% Si, 0.25 wt% Fe, 0.1 wt% B, 0.05 wt% rare earth element (Ce), ≤0.1 wt% unavoidable impurities, and aluminum as the balance.

[0132] Example B20

[0133] The method of Example B1 is followed, except that Er is used instead of Ce as the rare earth element.

[0134] Example B21

[0135] The method of Example B1 is followed, except that La is used instead of Ce as the rare earth element.

[0136] Example B22

[0137] The method of Example B1 is followed, except that Y is used instead of Ce as the rare earth element.

[0138] Example B23

[0139] The method of Example B1 is followed, except that the intermediate alloy A2 obtained in Example 2 is used to replace the intermediate alloy A1 obtained in Example 1.

[0140] Example B24

[0141] The method of Example B1 is followed, except that the intermediate alloy A3 obtained in Example 3 is used to replace the intermediate alloy A1 obtained in Example 1.

[0142] Comparative Example 1

[0143] The method of Example B1 was followed, except that no aluminum nitride was added.

[0144] Comparative Example 2

[0145] The method of Example B1 is followed, except that the graphene is not prepared as an intermediate alloy, but is directly smelted.

[0146] Comparative Example 3

[0147] The method of Example B1 is followed, except that step S6 is not performed, that is, the copper-plated graphene is directly melted without being coated with aluminum powder.

[0148] Comparative Example 4

[0149] The method of Example B1 is followed, except that step S5 is not performed, that is, the graphene is directly mixed and sintered with aluminum powder without copper plating.

[0150] Test Case

[0151] The electrical conductivity, tensile strength, ultimate heat-resistant temperature and elongation of the aluminum alloy wires prepared in the examples and comparative examples were tested. The test results are shown in Table 2.

[0152] Conductivity (% IACS): Tested in accordance with "Conductivity Test Standard GB / T 3955-2009 Electrical Round Aluminum Wire".

[0153] Elongation (%): Tested in accordance with "Mechanical Testing Standard GB / T 228.1-2010 Metal Material Tensile Test".

[0154] Tensile strength (MPa): Tested in accordance with "Mechanical Testing Standard GB / T 228.1-2010 Metal Material Tensile Test".

[0155] The testing method for the ultimate heat resistance temperature (°C) is: keep the aluminum alloy wire at different temperatures for 1h, then cool it to room temperature, test its tensile strength as T1, and its tensile strength before heating and insulation is T0, and calculate the high-temperature retention rate of strength, where the calculation method of the high-temperature retention rate of strength is T1÷T0×100%. When the high-temperature retention rate of strength is greater than 90%, the corresponding highest temperature is taken as its ultimate heat resistance temperature.

[0156] Table 2

[0157]

[0158]

[0159] It can be seen from Table 2 that the aluminum alloy wire obtained according to the technical solution described in the embodiment of the present invention has high conductivity, tensile strength, ultimate heat-resistant temperature and elongation.

[0160] It can be seen from Examples 1-4 that as the Fe content gradually increases, the conductivity first increases and then decreases. This is because a small amount of Fe can react with Si to precipitate, reducing the amount of Si dissolved in aluminum. However, when the Fe content increases relative to Si, Al3Fe will increase, resulting in additional resistance, so the conductivity decreases.

[0161] It can be seen from Examples 5-11 that as the amount of copper-plated graphene added gradually increases, the conductivity of the material can be effectively improved. However, since the scales in the X and Y directions are at the micron level, the improvement of strength by graphene is limited, and a large amount of addition will seriously reduce the elongation of the final wire.

[0162] It can be seen from Examples 12-16 and Comparative Example 3 that when the AlN content exceeds 1 wt %, the material strength is not significantly improved, but the elongation is severely reduced due to the agglomeration of particles.

[0163] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A master alloy, characterized in that: The master alloy contains a copper-plated carbon component and aluminum coated on the outside of the copper-plated carbon component, wherein the copper-plated carbon component contains a carbon component and a copper plating layer formed on the surface of the carbon component.

2. The master alloy according to claim 1, characterized in that In the master alloy, the content of the copper-plated carbon component is ≤40% by volume, with aluminum being the balance; Preferably, in the copper-plated carbon component, the mass fraction of Cu element on the surface of the carbon component is 35-60%.

3. The master alloy according to claim 1 or 2, characterized in that: The carbon component is graphene and / or carbon nanotube.

4. A method for preparing a master alloy, characterized in that: The method includes: (1) forming a copper plating layer on the surface of the conductive carbon material to obtain a modified conductive carbon material; (2) Mixing the modified conductive carbon material with aluminum powder, making embryos, and sintering.

5. The method according to claim 4, characterized in that In step (1), the conductive carbon material is graphene and / or carbon nanotubes; Preferably, the graphene sheet has a diameter of 10-25 μm and a thickness of ≤50 nm; Preferably, the carbon nanotubes have a diameter of 2-10 nm and a length of 1-20 μm.

6. The method according to claim 4 or 5, characterized in that: In step (1), the process of forming a copper plating layer on the surface of the conductive carbon material comprises: purifying and dispersing, roughening, sensitizing, activating and chemically copper plating the conductive carbon material in sequence; Preferably, the operating conditions of the chemical copper plating include: the pH value of the chemical plating solution is 11.5-12, the temperature of the chemical plating is 45-100° C., and the time is 30-70 min.

7. The method according to claim 4, characterized in that In step (2), based on the total amount of the modified conductive carbon material and the aluminum powder, the amount of the modified conductive carbon material is 20-40 volume %.

8. The method according to claim 4 or 7, characterized in that: In step (2), the particle size of the aluminum powder is ≤100 um.

9. The method according to claim 4, characterized in that In step (2), the sintering conditions include: temperature of 400-600° C. and time of 0.5-1.5 h.

10. An aluminum alloy raw material composition, characterized in that: The composition comprises aluminum blocks, aluminum alloy blocks, ceramic particles and master alloys; The master alloy is the master alloy described in any one of claims 1 to 3 or the master alloy prepared by the method described in any one of claims 4 to 9.

11. The composition according to claim 10, characterized in that The ceramic particles are selected from one or more of AlN, B4C and TiC; Preferably, the particle size of the ceramic particles is 10-50 nm.

12. An aluminum alloy prepared from the composition according to claim 10 or 11, characterized in that: The aluminum alloy contains 0.1-2.5 wt % of copper-plated carbon components, 0.1-2 wt % of ceramic components, ≤0.1 wt % of Si, ≤0.25 wt % of Fe, 0.01-0.1 wt % of B, 0.005-0.05 wt % of rare earth elements, ≤0.1 wt % of inevitable impurities and the balance of Al.

13. The aluminum alloy according to claim 12, characterized in that The carbon component in the copper-plated carbon component is graphene and / or carbon nanotubes; Preferably, the ceramic component is selected from one or more of AlN, B4C and TiC; Preferably, the rare earth element is selected from one or more of Er, La, Ce and Y.

14. A method for preparing the aluminum alloy according to claim 12 or 13, characterized in that: The method comprises: melting an aluminum block, an aluminum alloy block, ceramic particles and a master alloy.

15. The method according to claim 14, characterized in that The smelting process comprises: melting the aluminum block, the aluminum alloy block, the ceramic particles and the master alloy at 680-730° C., and then refining at 650-750° C.

16. An aluminum alloy wire, characterized in that: The aluminum alloy wire is made of the aluminum alloy described in claim 12 or 13, or the aluminum alloy prepared by the method described in claim 14 or 15.

17. The aluminum alloy wire according to claim 16, characterized in that: The aluminum alloy wire has a conductivity of ≥60% IACS, a tensile strength of ≥270 MPa, an ultimate heat-resistant temperature of ≥310° C., and an elongation of ≥1%.

Citation Information

Cited By

  • Intermediate alloy and aluminum alloy, preparation methods therefor, and aluminum alloy conductor

    WO2025218524A1